Studies in symbolic interaction. Vol. 35 - Denzin, Norman K. (Bingley, U.K. : Emerald, 2010)
The essays in this bi-annual series consist of original research and theory within the general sociological perspective known as symbolic interactionism. Longer than conventional journal-length articles, the essays wed mico and macro concerns within a qualitative, ethnographic, autoethnographic and performance studies orientation. International in scope, the series draws upon the work of urban ethnographers, interpretive, constructionist, ethnomethodological, critical race, postcolonial, feminist, queer, and cultural studies traditions.
Introduction : the impact of popular music on symbolic interaction / Joe Kotarba -- Introduction : music and identity / Christopher Schneider -- The group ethic in the improvising jazz ensemble : a symbolic interactionist analysis of music, identity and social context / Will Gibson -- Established Latino music scenes : authenticity and insincerity / Kathryn M. Nowotny, Jennifer L. Fackler, Gianncarlo Muschi, Carol Vargas, Lindsey Wilson & Joe A. Kotarba -- Authenticating identity work : accounts of underground country musicians / Jason Eastman -- Introduction : spaces of musical interaction : subcultures, scenes, and communities / Robert Owen Gardner -- Brutal belonging in Melbourne's grindcore scene / Rosemary Overell -- Musical genre as a gendered process : authenticity in extreme metal / Ben Hutcherson and Ross Haenfler -- Digging a river downstream : producing emergence in music / Nick Dempsey -- Teaching the art of playing with career-coupling relationships in the virtuoso world / Izabela Wagner -- Introduction : music in (inter)action / John Bryce Merrill -- Noise in action : the sonic (de)construction of art worlds / Carey Sargent -- Driving to the beat of one's own hum : automobility and musical listening / Michael Walsh -- Music, symbolic interaction and study abroad / J. Patrick Williams -- Grandmamma, what great ears you have! (Cross-generational musical interaction and the discovery of silence) / Aljosa Puzar -- Becoming yellow / Sayuri Arai -- Subculture and myth : the case of Robert Johnson in the 1920s-30s US South / William F. Danaher -- LeRoy and me / John M. Johnson -- Competing with her mother-in-law : the intersection of control management and emotion management in sport families / Steven M. Ortiz -- The futureless past / Michael A. Katovich -- G.H. Mead's intimations of dialogue and narrative in social becoming with others / William K. Rawlins.
Print version record
Keywords: Social Science -- Anthropology -- Cultural; Social Science -- Ethnic Studies -- General; Social Science -- Popular Culture; Symbolic interactionism